The The Strategy Analysis of Empowerment for Women Farmers Group Kedurus in Surabaya City - Kurniasari, Dwiyana Anela; Didik Daryanto; Siti Alimah; Jaka Larasati; Muhammad Kahvi (Agricultural Science, 2024)
In this research we will look at socio-economic conditions and ultimately analyze what strategies are appropriate and effective for women farming groups in Kedurus, Surabaya city. The aim of the research is to first explain the socio-economic conditions that exist among members of the women farmer group in Kedurus. Second, analyze and describe how empowerment strategies are appropriate to the needs, characteristics and abilities of women farmer group members in Kedurus. This research began in July and ended in August 2023. The objects of this research were 28 female farmer members in the Kedurus. This research uses a census method where all members are the object of research. This research uses SWOT analysis to describe how empowerment strategies suit the needs, characteristics and abilities of women farmer group members in Kedurus.